Republic Of Uzbekistan Military Prosecutor's Office (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article describes in detail the reforms, changes and innovations implemented in the field of the Prosecutor's Office of the Republic of Uzbekistan.